2019
DOI: 10.5624/isd.2019.49.3.219
|View full text |Cite
|
Sign up to set email alerts
|

Determination and classification of intraoral phosphor storage plate artifacts and errors

Abstract: PurposeThe aim of this study was to determine the reasons and solutions for intraoral phosphor storage plate (PSP) image artifacts and errors, and to develop an appropriate classification of the artifacts.Materials and MethodsThis study involved the retrospective examination of 5,000 intraoral images that had been obtained using a phosphor plate system. Image artifacts were examined on the radiographs and classified according to possible causative factors.ResultsArtifacts were observed in 1,822 of the 5,000 im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…The knowledge of the impact of several uses of a PSP receptor is necessary because when image quality is compromised, the radiographic diagnosis can be negatively affected 1 , 14 , 15 . Previous studies have reported that multiple exposures to X-rays and scanning caused a decrease in the pixel gray values of the resulting images 8 , 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge of the impact of several uses of a PSP receptor is necessary because when image quality is compromised, the radiographic diagnosis can be negatively affected 1 , 14 , 15 . Previous studies have reported that multiple exposures to X-rays and scanning caused a decrease in the pixel gray values of the resulting images 8 , 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Chiu et al [12] divided artifacts into three groups: operator errors, scanning errors, and PP defects. Deniz & Kaya [13] classified artifacts into six groups based on artifacts causes: operator errors, superimposition, ambient light errors, plate errors (physical deformations and contamination), scanner, and software errors. Hasan et al [9] divided artifacts into 2 groups: technical and image processing errors.…”
Section: Discussionmentioning
confidence: 99%
“…These artifacts can arise from any factors that disrupt, interrupt, decrease, or limit the performance of the scanner. To prevent this artifact, it is necessary to implement appropriate electromagnetic shielding, use the correct voltage source, ensure an uninterrupted power supply, and regularly maintain the scanner [10,13]. In a study conducted at two different institutes, Tashiro et al [8] determined a browser error rate of 52% in one institute.…”
Section: Discussionmentioning
confidence: 99%
“…[7] The color of most metal oxides is usually blue, such as V 2 O 5 [8][9][10][11] and WO 3 , [12][13][14][15] which can have luminescent properties by doping with other element to form germanate based phosphor, phosphate based phosphor, stannate based phosphor, titanate based phosphor, and borate based phosphor. [16][17][18] Barium magnesium silicate (BMS)-based phosphors are inorganic phosphors that have a long history and promising applications in many emerging fields. [19][20][21][22][23] The team of Kunming University of science and technology found that the photochromism and Photoluminescence of BaMgSiO 4 : Bi 3+ ceramics can meet the requirements of optical storage media.…”
Section: Introductionmentioning
confidence: 99%